TRANSLATION STRATEGY OF CULTURAL TERMS IN THE SUBJECT OF THE FILM "KUCUMBU TUBUH INDAHKU" AS A FORM OF RESISTANCE AND NEGOTIATION - Miftah Farhantia Zamroni; Tatang Hariri (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study examines the translation strategies of cultural terms in the subtitles of a film entitled “Kucumbu Tubuh Indahku” (Memories of My Body) by Garin Nugroho, focusing on their role as acts of cultural resistance and negotiation. The research aims to (1) identify and describe the strategies used to translate culture-specific terms, (2) analyze how these strategies reflect tendencies toward foreignization (resistance) and domestication (negotiation), and (3) interpret their contribution to the construction of character identity and the representation of Javanese culture to international audiences. This research employs a descriptive qualitative method with a comparative approach. The primary data consists of two subtitle transcripts of the same movie, analyzed using Newmark's (1988) procedures for translating cultural terms, Gottlieb's (1992) subtitle strategies, Venuti's (1995) domestication and foreignization ideology, and the framework of social actor representation. The analysis reveals 85 culture-specific items distributed across five categories: social culture, ecology, social organizations, gestures and habits, and material culture. The most frequently applied strategies are transference, functional equivalence, paraphrase, adaptation, and substitution. The findings indicate that foreignization functions as cultural resistance by preserving key terms such as warok, lengger, and gemblak, while domestication functions as negotiation through strategies such as generalization, condensation, and adaptation. Drawing on social actor representation, the study shows that cultural identity in subtitles is articulated through practices of nomination, categorization, and functionalization, which illustrates how both the characters and Javanese culture are recontextualized in a global setting. Overall, the study argues that subtitling is not merely a linguistic transfer but an ideological arena that actively shapes perceptions of identity and cultural representation in international discourse.